In Vitro Activity of Iclaprim against Methicillin-Resistant Staphylococcus aureus Nonsusceptible to Daptomycin, Linezolid, or Vancomycin: A Pilot Study - David B. Huang; Stephen Hawser; Curtis G. Gemmell; Daniel F. Sahm (Canadian Journal of Infectious Diseases and Medical Microbiology)
Iclaprim is a bacterial dihydrofolate reductase inhibitor in Phase 3 clinical development for the treatment of acute bacterial skin and skin structure infections and hospital-acquired bacterial pneumonia caused by Gram-positive bacteria. Daptomycin, linezolid, and vancomycin are commonly used antibiotics for these indications. With increased selective pressure to these antibiotics, outbreaks of bacterial resistance to these antibiotics have been reported. This in vitro pilot study evaluated the activity of iclaprim against methicillin-resistant Staphylococcus aureus (MRSA) isolates, which were also not susceptible to daptomycin, linezolid, or vancomycin. Iclaprim had an MIC ≤ 1 µg/ml to the majority of MRSA isolates that were nonsusceptible to daptomycin (5 of 7 (71.4%)), linezolid (26 of 26 (100%)), or vancomycin (19 of 28 (66.7%)). In the analysis of time-kill curves, iclaprim demonstrated ≥ 3 log10 reduction in CFU/mL at 4–8 hours for tested strains and isolates nonsusceptible to daptomycin, linezolid, or vancomycin. Together, these data support the use of iclaprim in serious infections caused by MRSA nonsusceptible to daptomycin, linezolid, or vancomycin.